2018
DOI: 10.3390/rs10050695
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Modeling Framework for Characterising Uncertainty in Large Datasets: Application to Ocean Colour

Abstract: Uncertainty estimation is crucial to establishing confidence in any data analysis, and this is especially true for Essential Climate Variables, including ocean colour. Methods for deriving uncertainty vary greatly across data types, so a generic statistics-based approach applicable to multiple data types is an advantage to simplify the use and understanding of uncertainty data. Progress towards rigorous uncertainty analysis of ocean colour has been slow, in part because of the complexity of ocean colour proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For biogeochemical variables, Amin et al (2015) assessed GOES satellite-based ocean color products using in situ networks (Amin et al, 2015). Land et al (2018) used a database of satellite in situ matchups to generate a statistical model of satellite uncertainty as a function of its contributing variables for ocean color chlorophyll-a and showed that most errors are correctable biases (Land et al, 2018). Martínez-Vicente et al (2017) examined the differences among phytoplankton carbon (Cphy) estimations from six satellite ocean color algorithms by comparison with in situ estimates, and large (>100%) biases have been found (Martínez-Vicente et al, 2017).…”
Section: Blended Satellite and In Situ Products And Servicesmentioning
confidence: 99%
“…For biogeochemical variables, Amin et al (2015) assessed GOES satellite-based ocean color products using in situ networks (Amin et al, 2015). Land et al (2018) used a database of satellite in situ matchups to generate a statistical model of satellite uncertainty as a function of its contributing variables for ocean color chlorophyll-a and showed that most errors are correctable biases (Land et al, 2018). Martínez-Vicente et al (2017) examined the differences among phytoplankton carbon (Cphy) estimations from six satellite ocean color algorithms by comparison with in situ estimates, and large (>100%) biases have been found (Martínez-Vicente et al, 2017).…”
Section: Blended Satellite and In Situ Products And Servicesmentioning
confidence: 99%
“…Improved results may be achieved in the future by using a longer time series to better constrain the EOFs near long gaps, or by using a longer temporal covariance matrix filter [47]. Additionally, the quality of input data is an important consideration for using DINEOF and is affected by the inherited uncertainties of the chla sat [57]. In this study, quality control prior to DINEOF processing included standard ocean color flags, a reduced straylight filter (3 × 3), removal of chla sat pixels exceeding 40.00 mg m −3 (Section 2.2.1), and removal of scenes and pixels with less than 2% ocean coverage (Section 2.3).…”
mentioning
confidence: 99%